When Policy Produces Moral Distress: Reclaiming Conscience. Issue 2 (March 2016) - Berlinger, Nancy
Abstract: For too long, bioethics has followed law in reducing "conscience" to "conscientious objection, " in other words, to laws and policies permitting and protecting refusal. In "Reframing Conscientious Care: Providing Abortion Care When Law and Conscience Collide, " Mara Buchbinder and colleagues draw our attention to one dimension of the problem of reducing conscience to refusal to provide certain forms of medical care: what about the conscience problems experienced by the professionals who are attempting to provide safe, effective health care that includes services that others associate with conscientious objection? In seeking to disrupt a specific medical practice—one that is legal, desired by the patient, and conducted in accordance with medical standards—North Carolina House Bill 854, The Woman's Right to Know Act, and laws like it, appear to be designed to produce moral distress in physicians and other professionals involved in the provision of abortions. For abortion providers in North Carolina and other states, conscientious objection to the mandates of laws like HB 854 isn't a realistic option. So what can bioethics offer to professionals bound by such laws? We can start by reclaiming the idea of "conscience" as something that can say "yes" to providing health care.